Collaborative Testing of Web Services - Zhu, Hong; Zhang, Yufeng (IEEE transactions on services computing, 2012)
Software testers are confronted with great challenges in testing Web Services (WS) especially when integrating to services owned by other vendors. They must deal with the diversity of implementation techniques used by the other services and to meet a wide range of test requirements. However, they are in lack of software artifacts, the means of control over test executions and observation on the internal behavior of the other services. An automated testing technique must be developed to be capable of testing on-the-fly nonintrusively and nondisruptively. Addressing these problems, this paper proposes a framework of collaborative testing in which test tasks are completed through the collaboration of various test services that are registered, discovered, and invoked at runtime using the ontology of software testing STOWS. The composition of test services is realized by using test brokers, which are also test services but specialized in the coordination of other test services. The ontology can be extended and updated through an ontology management service so that it can support a wide open range of test activities, methods, techniques, and types of software artifacts. The paper presents a prototype implementation of the framework in semantic WS and demonstrates the feasibility of the framework by running examples of building a testing tool as a test service, developing a service for test executions of a WS, and composing existing test services for more complicated testing tasks. Experimental evaluation of the framework has also demonstrated its scalability.